Men and Women in The Distribution of Inheritance in Mandar, West Sulawesi, Indonesia - Rahman, Ulfiani; Idham, Idham; Dalif, M.; Makmur, Makmur; Sewang, Anwar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
In general, there are two patterns of inheritance distribution in Indonesia, based on Islamic and customary inheritance laws. This research specifically focused on the distribution of inheritance for men and women in Mandar by scoping the research area in Polewali Mandar Regency, West Sulawesi Province. This research is an empirical legal study using the sociology of law approach. Data collection techniques were obtained through literature study and interviews. The results showed that the Mandar people who lived in Polewali Mandar, West Sulawesi Province, considered that whether son or daughter earned the same sharing, there was no difference. The view that puts the same position between the two has influenced the legal treatment of inheritance. The distribution of inheritance in Mandar, especially for sons and daughters, was found in two patterns, namely, using Islamic inheritance patterns and customary inheritance patterns. This customary inheritance pattern is practiced in the form that they are no longer able to define, whether it is in the form of Islamic law or customary law, dividing the inheritance to their children to be managed by themselves, and some have shared the inheritance with their children, but the heir still manages the assets, and the house of the parents belongs to the youngest child, without distinguishing between the youngest son or the youngest daughter.